1992
DOI: 10.1007/bf02171759
|View full text |Cite
|
Sign up to set email alerts
|

Levels of human serum granulocyte colony-stimulating factor and granulocyte-macrophage colony-stimulating factor under pathological conditions

Abstract: Levels of serum granulocyte colony-stimulating factor (G-CSF) and granulocyte-macrophage colony-stimulating factor (GM-CSF) in patients with various leukocyte disorders were estimated by enzyme-linked immunosorbent assay (ELISA). Some cases of acute myelogenous leukemia and aplastic anemia showed elevated serum levels of G-CSF and/or GM-CSF, whereas almost all of 23 healthy controls showed G-CSF and GM-CSF levels lower than 100 pg/ml. High levels of both types of CSF were noted in patients with granulocytosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Cytokine levels were similar in the two groups. Previous studies have shown that G-CSF, IL-6, erythropoietin, and TNF-ax are elevated in patients with myelodysplastic syndromes (11)(12)(13) (36), which recent studies suggest plays an important role in the development of leukemias and lymphomas (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytokine levels were similar in the two groups. Previous studies have shown that G-CSF, IL-6, erythropoietin, and TNF-ax are elevated in patients with myelodysplastic syndromes (11)(12)(13) (36), which recent studies suggest plays an important role in the development of leukemias and lymphomas (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine measurements were prioritized on the basis of alterations previously detected in patients with the myelodysplastic syndrome (11)(12)(13). Plasma levels of granulocyte colony stimulating factor (G-CSF) and granulocyte-macrophage colony-stimulating factor both tend to be elevated in patients with aplastic anemia (13).…”
Section: Subject Enrollmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased numbers of monosomy 7 cells relative to diploid cells were evident in cultures after 4 days at low GCSF concentrations, but significantly more monosomy 7 cells were seen growing at very high GCSF concentrations, in the range of those present in the circulation of patients with marrow failure (11,14) (Fig. 1C).…”
Section: Gcsf Promotes Expansion Of Preexisting Monosomy 7 Clonesmentioning
confidence: 93%
“…In one study of marrow-failure patients, only 28% of chromosomal abnormalities detected by FISH were observed by conventional cytogenetics (10). GCSF levels are generally an order of magnitude higher in severe AA than in neutropenia of other origins (11,12). An increased prevalence of monosomy 7 among untreated cases could, therefore, be explained by high endogenous levels of GCSF in AA.…”
mentioning
confidence: 99%